The contribution of higher education institutions to the SDGs: An evaluation of sustainability reporting practices - Fabio Caputo; Lorenzo Ligorio; Simone Pizzi (Administrative Sciences, 2021)
The introduction of Agenda 2030 has impacted the public and private sectors. Agenda 2030 is a document that aims to promote collaboration and partnership between countries and the population for the achievement of 17 SDGs, which cover all the three dimensions of sustainability: environmental, social, and economic. Within the public organizations, higher education institutions (HEIs) have shown certain attention on the topic. In particular, for many HEIs, the publication of sustainability reports has represented an instrument to disclose and publicize their commitment to the 17 Sustainable Development Goals (SDGs). To shed light on the highly fragmented panorama of the disclosure of SDGs in the context of HEIs, the present study employed a content analysis on publicly available sustainability reports published only by the HEIs that adopted the GRI Standards as reporting guidelines. The results show the centrality of the social and environmental issues within the disclosed information. Moreover, the provision of a thematic analysis on the SDGs disclosure sections revealed the interest of the sampled HEIs in increasing the level of involvement of their stakeholders.
Keywords: 350; Global Reporting Initiative; higher education; sustainability reporting; Sustainable Development Goals; thematic analysis